2012
DOI: 10.1021/ja307697j
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Defined Graphene Nanoribbons with High Lateral Extension

Abstract: Oxidative cyclodehydrogenation of laterally extended polyphenylene precursor allowed bottom-up synthesis of structurally defined graphene nanoribbons (GNRs) with unprecedented width. The efficiency of the cyclodehydrogenation was validated by means of MALDI-TOF MS, FT-IR, Raman, and UV-vis absorption spectroscopies as well as investigation of a representative model system. The produced GNRs demonstrated broad absorption extended to near-infrared region with the optical band gap of as low as 1.12 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
200
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(211 citation statements)
references
References 40 publications
10
200
0
1
Order By: Relevance
“…However, these and other methods mentioned before are not suitable for the synthesis of graphene needed for the preparation of graphene-based nanocomposites that usually require large amounts of graphene sheets preferably with modified surface structure. 5,9,58,59 While mechanical exfoliation using scotch-tape is a laborious procedure and rarely leads to a good quality of individual graphene sheets, epitaxial growth requires highvacuum conditions and specialized, expensive fabrication system to generate films on small areas. Still, the production of graphene monolayers with large surface areas has been attainable due to the more recent advances in CVD techniques, the uniform growth of single layers of graphene is still a challenge and indeed suitable methods have yet to be fully developed.…”
Section: Figmentioning
confidence: 99%
“…However, these and other methods mentioned before are not suitable for the synthesis of graphene needed for the preparation of graphene-based nanocomposites that usually require large amounts of graphene sheets preferably with modified surface structure. 5,9,58,59 While mechanical exfoliation using scotch-tape is a laborious procedure and rarely leads to a good quality of individual graphene sheets, epitaxial growth requires highvacuum conditions and specialized, expensive fabrication system to generate films on small areas. Still, the production of graphene monolayers with large surface areas has been attainable due to the more recent advances in CVD techniques, the uniform growth of single layers of graphene is still a challenge and indeed suitable methods have yet to be fully developed.…”
Section: Figmentioning
confidence: 99%
“…Several recent studies have focused on the synthesis of GNRs by the bottom-up approaches that rely on building GNRs from smaller molecular species. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] The resulting GNRs are very narrow (typically with widths, w < 2 nm) and have atomically precise edges, which is very important for potential applications. [3][4][5][6]21,22 One type of synthetic GNRs that has received considerable theoretical [23][24][25] and experimental attention 9,16,19,20,26 is the chevron-like GNR that has a very distinct periodic structure (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, producing GNRs with tailor-made predefined widths, edge structure geometries and suitable solubility constitutes an important challenge for synthetic chemists. Bottom-up approaches reported to date include organic synthesis in solution via crosscoupling of the appropriate organic building-blocks followed by the dehydrogenation of the resulting oligomers, 37,38,[40][41][42][43][44][45][46][47] the conversion of precursors inside CNTs, 48,49 and surface-assisted polymerization with subsequent dehydrogenation in an ultra-high vacuum environment. 39,50,51 Although these bottom-up methods provide GNRs with a defined edge structure, they so far suffer from the inability to afford GNRs having variable widths at large scales, owing to the low solubility of the synthesized GNRs, and/or the need for highly-specialized instrumentation.…”
Section: Methodsmentioning
confidence: 99%
“…42 Two years later, the same research group reported the synthesis of a series of nanoribbons derived from polyphenylene precursors with a non rigid kinked backbone (Scheme 6, GNR5a-c type) 43 that showed higher solubility compared to the previously reported rigid linear poly(paraphenylene) systems. 42,52 For the preparation of the precursor polymers, microwave assisted Suzuki-Miyaura coupling polymerization was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation